Amazing gorillas! - Thomson, Sarah L.; Wildlife Conservation Society (New York, N.Y.) (New York : HarperCollins, 2005)
Presents a children's book for young readers on gorillas, and discusses their habitat, how they live, what they eat, and the ways in which gorillas and humans are alike.
"2, reading with help.".
3.7
K-3
Keywords: Gorilla -- Juvenile literature; Gorilla; Gorillas; Gorilla